1993
DOI: 10.1039/p29930001561
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of nitrosation of clonidine: a bridge between nitrosation of amines and ureas

Abstract: Nitrosation of clonidine has been studied kinetically both in acid medium (with nitrous acid) and in basic medium (with 2.2-dichloroethyl nitrite). The reactive form in acid medium was found t o be the protonated clonidine (pK, 8.18). The absence of catalysis by halides or thiocyanate, the existence of general base catalysis, and the measured solvent isotope effect all indicate that the reaction mechanism is different from that for the N-nitrosation of amines. Specifically, kinetic results indicate that the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
(3 reference statements)
2
8
0
Order By: Relevance
“…The slopes of the plot display a familiar catalytic sequence, Cl À < Br À < SCN À , found in nitrosation reactions. This behaviour indicates that, unlike other guanidines, [18][19][20] nitrosation of AG is subject to nucleophile catalysis, Figure 1. Influence of aminoguanidine concentration upon k obs , (*) and seems to confirm a mechanism for AG nitrosation that is similar to that for amines, i.e.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The slopes of the plot display a familiar catalytic sequence, Cl À < Br À < SCN À , found in nitrosation reactions. This behaviour indicates that, unlike other guanidines, [18][19][20] nitrosation of AG is subject to nucleophile catalysis, Figure 1. Influence of aminoguanidine concentration upon k obs , (*) and seems to confirm a mechanism for AG nitrosation that is similar to that for amines, i.e.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies on nitrosation of guanidines of different basicity [18][19][20] showed that their kinetic behaviour differs from that of most amines. In order to explore the apparent differences between amines and guanidines, we studied the influence of the usual catalysts of the nitrosation process on the rate of the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation makes the kinetic study of the nitrosation of Gs, molecules that combine characteristics of both functional groups, very interesting and provides a bridge between amines and ureas. In fact a study of the nitrosation of clonidine [15] (a guanidine with hypotensive properties) has shown than in acid medium, the mechanism shows parallels with that found for ureas. However, in basic medium, the kinetic behaviour is similar to that exhibited by amines.…”
Section: Introductionmentioning
confidence: 83%